Platelets Protect Cardiomyocytes from Ischemic Damage - Tony G. Walsh; Alastair W. Poole (TH Open, 2017)
Platelets are classically known for their roles in bleeding control and occlusive thrombus formation causing ischemic tissue damage. Recently, nonclassical roles for platelets have been described, many of which may be mediated by the heterogeneous cargo that platelets secrete from granular stores upon activation. Using an in vitro model of ischemic injury to ventricular cardiomyocytes, we observed that platelets, through secreted factors, delayed the rate of cardiomyocyte death during ischemia. This protective effect appeared independent of platelet dense granule cargo, but required α-granule components stromal cell-derived factor-1α and transforming growth factor-β1. Protein kinase C activity within cardiomyocytes was responsible for mediating the protective signals initiated by the released platelet cargo. Importantly, pretreating platelets with a P2Y12 antagonist, but not the cyclooxygenase inhibitor aspirin, substantially attenuated this protective effect. These findings therefore reveal a paradoxically protective role for platelet activation during cardiac ischemia and could have important implications for the use of antiplatelet therapeutics in the management of myocardial infarction.